Community participation: exploring legitimacy in socio-ecological systems for environmental water governance. Issue 1 (2nd January 2019) - Godden, Lee; Ison, Ray
ABSTRACT: Environmental water governance is a highly contested space in which the legitimacy of institutional and legal models for water managing relies heavily, but indirectly, upon the effectiveness of community engagement. Accordingly, this article explores the relationship between legitimacy and participatory forms of decision-making in relation to public institutions with responsibility for environmental water governance in Australia. This examination explores the role that law and systems theory, working as transdisciplinary, theoretically informed praxis, can bring to an understanding of socio-ecological systems for environmental water governance. The Olifants River case study in South Africa provides a counterpoint to the investigation of environmental water institutions in the Murray–Darling Basin in Australia. As a grounded analysis of emergent forms of community engagement, the South African model illustrates how systemic affordances can introduce greater flexibility and choice, and thereby enhance the legitimacy of environmental water governance.